Predicting Protein-protein Interaction Using Amino Acid Sequence Information: A Computational Approach - Shoyaib, Mohammad; Abdullah-Al-Wadud, M.; Baker, Syed Murtuza; Islam, Mohammad Nurul; Chae, Oksam (Plant Tissue Culture and Biotechnology, 2010)
An improved computational approach which implements a protein-protein interaction prediction system based on the sequence information of a protein has been presented. A Support Vector Machine (SVM) is trained with this sequence information to predict the interactions. This interaction prediction technique exhibits 79.81% accuracy over a wide range of data, which is a significant improvement over other conventional computational protein-protein interaction prediction methods. Key words: Protein-protein interaction, Amino acid sequence, Computational approach D.O.I. 10.3329/ptcb.v20i1.5963 Plant Tissue Cult. & Biotech. 20(1): 37-45, 2010 (June)